Targeted treatment of solid tumors in pediatric precision oncology - Bertacca, Ilaria; Pegoraro, Francesco; Tondo, Annalisa; Favre, Claudio (Frontiers in Oncology, 2023)
The treatment of childhood solid cancer has markedly evolved in recent years following a refined molecular characterization and the introduction of novel targeted drugs. On one hand, larger sequencing studies have revealed a spectrum of mutations in pediatric tumors different from adults. On the other hand, specific mutations or immune dysregulated pathways have been targeted in preclinical and clinical studies, with heterogeneous results. Of note, the development of national platforms for tumor molecular profiling and, in less measure, for targeted treatment, has been essential in the process. However, many of the available molecules have been tested only in relapsed or refractory patients, and have proven poorly effective, at least in monotherapy. Our future approaches should certainly aim at improving the access to molecular characterization, to obtain a deeper picture of the peculiar phenotype of childhood cancer. In parallel, the implementation of access to novel drugs should not only be limited to basket or umbrella studies, but also to larger, multi-drug international studies. In this paper we reviewed the molecular features and the main available therapeutic options in pediatric solid cancer, focusing on available targeted drugs and ongoing investigations, aiming at providing a useful tool to navigate the heterogeneity of this promising but complex field.